Cutting ability of nickel-titanium rotary systems ProTaper, Mtwo and K3 - Sergio Herrero Moraes; Marcelo Gonçalves; Mário Tanomaru Filho; Idomeo Bonetti Filho (Revista Sul-Brasileira de Odontologia, 2013)
Nickel-titanium rotatory systems should remove dentin during the root canal preparation to promote the enlargement and tapered shape with continuously narrowing towards the apex. Objective: The aim of this study was to analyze the cutting ability of three NiTi rotatory systems (n = 12): ProTaper (group 1), Mtwo (group 2), and K3 (group 3). Material and methods: Thirty six maxillary molar teeth were weighted on an analytical balance before and after the rotatory preparation of the mesio-buccal root canal. Data was statistically analyzed by ANOVA and Tukey’s test with a significance level of 5%. Results: The results revealed the following mass differences (g) before and after the root canal preparation: ProTaper (group 1 – 0.0159 ± 0.004), Mtwo (group 2 – 0.0125 ± 0.002), and K3 (group 3 – 0.007 ± 0.003). Conclusion: ProTaper showed the highest cutting ability among the three tested nickeltitanium rotatory systems followed by Mtwo and K3.